P1.30 In High Cvd Risk Group Arterial Function Markers Correlate Weakly with Pwv and Aixhr75 As Exceptions - Navickas, R.; Ryliskyte, L.; Jakaitiene, A.; Visockiene, Z.; Badariene, J.; Laucevicius, A. (Artery research, 2012)
Background With more recent publications it is becoming obvious that arterial wall function contributes to the cardiovascular disease (CVD) risk. Relatively few studies investigated high CVD risk subjects, where arterial wall function abnormalities are likely to be more pronounced with multiple risk factors. The aim of the study was to assess the relationship between arterial wall markers in a high CVD risk subjects. Methods A cross-sectional study included patients with metabolic syndrome but with no previous CVD. Arterial stiffness (aortic pulse wave velocity [PWV] augmentation index [AIx], carotid and ankle-brachial stiffness index [CSI and CAVI, respectively]), endothelial function (flow-mediated dilatation in brachial artery and finger [RHI]), and carotid intima-media thickness (CIMT) were measured. Univariate and multivariable association assessment between these parameters was performed. Results Among 3168 subjects (aged 55±5, 69% women) univariate analysis revealed that markers significantly (p<0.01, Pearson r>0.1) associated with PWV and AIx are CAVI and RHI, and PWV correlates with AIx. CSI was significantly associated only with CIMT. No significant interaction between other independent variables was observed. Interestingly, 2/3 of markers revealed higher correlations for male compared to female group. Traditional risk factors (gender, age, blood pressure, BMI etc.) explained only 12–34% of variability for PWV, AIx, and CSI. Conclusion In this high CVD risk group we did not find a definite/strong correlation between most of the arterial markers investigated, possibly because they reflect different stage of the same process or due to varying impact of different factors. Stronger inter-correlation of the arterial markers was observed in men.